PENGGUNAAN METODE DHCP SNOOPING DALAM MELAKUKAN PENCEGAHAHAN TERHADAP DHCP ROGUE DI LABORATORIUM TEKNIK INFORMATIKA - Willy Permana Putra; Muhamad Zulfikar Azis (Politeknik Negeri Indramayu, 2023)
Network connection has an important role for the community, especially for students of the Indramayu State Polytechnic Department of Informatics. which serves to assist practical activities, which are carried out at the Informatics Engineering Department Laboratory. DHCP Rogue is a threat that can occur on a network, which can deflect data packets that pass. This action can be done by an irresponsible person. Therefore, there is a need for network security to prevent threats from DHCP Rogue, to overcome this problem, a DHCP Snooping method is needed to prevent DHCP Rogue on the network. Given the threat, he carried out several stages by configuring DHCP Snooping, configuring the DHCP server, and monitoring the network using the Wireshark application. Which is implemented at the Informatics Engineering Laboratory, to maintain data packets that pass, and can find out if there is a DHCP Rogue in the network. In this article, the results of preventing DCHP Rogue can be handled using the DHCP Snooping method through testing results, and monitoring on the network